Periodic lateralized epileptiform discharges (PLEDs) in cerebral lupus correlated with white-matter lesions in brain MRI and reduced cerebral blood flow in SPECT - Aye, S.M.M.; Lim, K.S.; Ramli, N.M.; Tan, C.T. (Arnold Publishers (journals now owned by Sage), 2013)
This is a case report on an uncommon correlation between periodic lateralized epileptiform discharges (PLEDs) and white-matter lesions in cerebral lupus, and with a reduced cerebral blood flow (CBF) in single-photon emission computed tomography (SPECT). A 47-year-old woman with a long-term history of systemic lupus erythematosus (SLE) presented with a seizure followed by frontal lobe dysfunction clinically. An electroencephalogram (EEG) showed bilateral independent PLEDs in the frontal region. A magnetic resonance image of the brain showed white-matter changes in the frontal periventricular region. Cerebral angiogram did not reveal any evidence of vasculitis. A cerebral SPECT with tracer injected during the EEG showing PLEDs showed a reduction in CBF in the frontal regions. Clinical recovery was observed with intravenous immunoglobulin. This case shows that PLEDs can be seen with white-matter changes in SLE. Lupus (2013) 22, 510-514.